Pengaruh Promosi Media Sosial, Kualitas Produk Dan Brand Awareness Terhadap Keputusan Pembelian Poroduk Kosmetik Wardah Di Jakarta Selatan: The Influence of Social Media Promotion, Product Quality, and Brand Awareness on Wardah Cosmetic Product Purchase Decisions In the city of South Jakarta. - Nadiya Nurfazah Fadilah; Tri Lestari; Dian Berliansyah Putra (PT Cakrawarti Empat Proksi, 2026)
The rapid growth of Indonesia's cosmetic industry, along with the increasing use of social media, has intensified competition among cosmetic brands. This condition encourages companies to strengthen their social media promotion, product quality, and Brand Awareness strategies to influence consumers' purchasing decisions. This study aims to analyze the influence of social media promotion, product quality, and Brand Awareness on the purchasing decisions of Wardah cosmetic products in South Jakarta. This research employed a quantitative approach using a purposive sampling technique. The sample consisted of 100 respondents who were Wardah consumers in South Jakarta and had purchased Wardah products within the last six months. Data were collected through questionnaires distributed via Google Forms. Data analysis was conducted using SPSS version 26, including validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination analysis. The results indicate that social media promotion has a positive and significant effect on purchasing decisions, with a significance value of 0.013. Product quality also has a positive and significant effect on purchasing decisions, with a significance value of 0.017. Brand Awareness is the most dominant variable influencing purchasing decisions. Simultaneously, social media promotion, product quality, and Brand Awareness have a positive and significant effect on purchasing decisions, with a significance value of 0.000. The Adjusted R Square value of 0.937 indicates that these three independent variables explain 93.7% of the variation in purchasing decisions, while the remaining 6.3% is influenced by other factors outside the scope of this study.